Remote nucleophilic allylation by allylrhodium chain walking - Groves, Alistair; Martinez, Jose I.; Smith, Joshua J.; Lam, Hon Wai (Wiley, 2018)
Metal migration through a carbon chain is a versatile method for achieving remote functionalization. However, almost all known examples involve the overall net migration of alkylmetal species. Here, we report that allylrhodium species obtained from hydrorhodation of 1,3-dienes undergo chain walking toward esters, amides, or (hetero)arenes over distances of up to eight methylene units. The final, more highly conjugated allylrhodium species undergo nucleophilic allylation with aldehydes and an imine to give Z-homoallylic alcohols and amines, respectively.